Emetine, a potent alkaloid for the treatment of SARS-CoV-2 targeting papain-like protease and non-structural proteins: pharmacokinetics, molecular docking and dynamic studies. Issue 20 (29th November 2022) - Snoussi, Mejdi; Redissi, Alaeddine; Mosbah, Amor; De Feo, Vincenzo; Adnan, Mohd; Aouadi, Kaïss; Alreshidi, Mousa; Patel, Mitesh; Kadri, Adel; Noumi, Emira
Abstract: The main objective of this study is to find out the anti-SARS-CoV-2 potential of emetine by using molecular docking and dynamic simulation approaches. Interestingly, molecular docking studies suggest that Emetine showed significant binding affinity toward Nsp15 (-10.8  kcal/mol) followed by Nsp12 (-9.5  kcal/mol), RNA-dependent RNA polymerase, RdRp (-9.5  kcal/mol), Nsp16 (-9.4  kcal/mol), Nsp10 (-9.2  kcal/mol), Papain-like protein (-9.0  kcal/mol), Nsp13 (-9.0  kcal/mol), Nsp14 (-8.9  kcal/mol) and Spike Protein Receptor Domain (-8.8  kcal/mol) and chymotrypsin-like protease, 3CLpro (-8.5  kcal/mol), respectively, which are essential for viral infection and replication. In addition, molecular dynamic simulation (MD) was also performed for 140  ns to explore the stability behavior of the main targets and inhibitor complexes as well as the binding mechanics of the ligand to the target proteins. The obtained MD results followed by absolute binding energy calculation confirm that the binding of emetine at the level of the various receptors is more stable. The complex EmetineNSP15, mechanistically was stabilized as follows: Emetine first binds to the monomer, after, binds to the second inducing the formation of a dimer which in turn leading to the formation of complex that simulation stabilizes it at a value less than 5  Å. Overall, supported by the powerful and good pharmacokinetic data of Emetine, our findings with clinical trials may be helpful to confirm that Emetine could be promoted in the prevention and eradication of COVID-19 by reducing the severity in the infected persons and therefore can open possible new strategies for drug repositioning. Communicated by Ramaswamy H. Sarma